Applying the lessons learned from coronavirus disease 2019 to improve pneumonia management. Issue 2 (April 2021) - Waterer, Grant W.
Abstract : Purpose of review: Coronavirus disease 2019 (COVID-19) has produced an extraordinary amount of literature in a short time period. This review focuses on what the new literature has provided in terms of more general information about the management of community-acquired pneumonia (CAP). Recent findings: Measures taken to reduce the spread of COVID-19 have caused a significant drop in influenza worldwide. Improvements in imaging, especially ultrasound, and especially in the application of rapid molecular diagnosis are likely to have significant impact on the management of CAP. Therapeutic advances are so far limited. Summary: COVID-19 has taught us that we can do far more to prevent seasonal influenza and its associated mortality, morbidity and economic cost. Improvements in imaging and pathogen diagnosis are welcome, as is the potential for secondary benefits of anti-COVID-19 therapies that may have reach effect on respiratory viruses other than severe acute respiratory syndrome coronavirus 2. As community-transmission is likely to persist for many years, recognition and treatment of severe acute respiratory syndrome coronavirus 2 will need to be incorporated into CAP guidelines moving forward.